The Convergence Insufficiency Neuro-mechanism in Adult Population Study (CINAPS) Randomized Clinical Trial: Design, Methods, and Clinical Data. (2nd January 2020) - Alvarez, Tara L.; Scheiman, Mitchell; Santos, Elio M.; Morales, Cristian; Yaramothu, Chang; D'Antonio-Bertagnolli, John Vito; Biswal, Bharat B.; Gohel, Suril; Li, Xiaobo
ABSTRACT: Purpose : To describe the design and methodology of the Convergence Insufficiency Neuro-mechanism in Adult Population Study (CINAPS), the first randomized clinical trial (RCT) studying young adults with symptomatic convergence insufficiency (CI) using a combination of traditional clinical tests, objective eye movement recordings, and functional brain activities as outcome measures. Methods : In this double-masked RCT, binocularly normal controls (BNC) (N = 50) and CI patients (N = 50) are randomized into office-based vergence/accommodative therapy (OBVAT) or office-based placebo therapy (OBPT). Outcome measures included clinical signs and symptoms, phoria adaptation, forced fixation disparity curves, binocular rivalry, vergence and saccadic objective eye movements, and task-induced functional brain activities. This study is registered on ClinicalTrials.gov NCT03593031. Results : No significant baseline differences are observed between the BNC ( p > .4) or CI ( p > .3) participants assigned to OBVAT or OBPT for age, near point of convergence (NPC), positive fusional vergence (PFV), phoria at distance and near, amplitude of accommodation, or the Convergence Insufficiency Symptom Survey (CISS). Significant differences are observed between the CI and BNC cohorts at baseline measurements for NPC, PFV, difference in phoria from far to near, amplitude of accommodation, and CISS ( p < .001). For the CI patients, 26% had a comorbidity of accommodation insufficiency, and 16% self-reported ADHD. Conclusion : Features of the study design include the following: standardized diagnostic and office-based therapeutic intervention, placebo treatment arm, masked clinical outcome examinations, objective eye movement recordings, functional imaging, phoria adaptation, fixation disparity curves and binocular rivalry measurements.